Determining the mobility of polystyrene nano-plastic in saturated quartz Sand-Limestone porous media. (12th October 2022) - Ye, Xinyao; Cheng, Zhou; Wu, Ming; Hu, Bill X.; Mo, Cehui; Li, Qusheng; Wu, Jianfeng; Wu, Jichun; Hao, Yanru; Lu, Guoping
Graphical abstract: Highlights: Limestone (LT) has a significant effect on the mobility of PSNPs. 2D surfaces of DLVO interaction energy of PSNPs-PSNPs, PSNPs-QS and PSNPs-LT are obtained. The critical ionic strength related to PSNPs mobility is quantified. PSNPs mobility decreased with the mass fraction of LT, grain size of PSNPs and ionic strength. The kinetic parameters related to PSNPs mobility in QS-LT are highly correlated with DLVO energy barrier. Abstract: To investigate the transport of microplastics in mixed porous media, column experiments are conducted to investigate polystyrene nanoparticles (PSNPs) transport in saturated quartz sand (QS)-limestone (LT) porous media under different physicochemical conditions. The two-dimensional (2D) surface of DLVO interaction energy is calculated to quantify the continuous change of the DLVO energy barrier with ionic strength and predict the critical ionic strengths (CIS). Experimental results suggest the mobility of PSNPs is inhibited as the mass fraction of LT and grain size of PSNPs increases. However, PSNPs mobility is enhanced with initial concentration and flow velocity. Compared with monovalent cation (Na + ), divalent cation (Ca 2+ ) has a stronger charge shielding effect. Significantly, there is a significant correlation between the transport kinetic parameters of PSNPs and the DLVO energy barrier, which suggests 2D surface of DLVO interaction energy has a great applied potential in the prediction of nano-plastics behaviors in the natural subsurface environment.